2003
DOI: 10.2460/javma.2003.222.54
|View full text |Cite
|
Sign up to set email alerts
|

Results of single-session bilateral triple pelvic osteotomy with an eight-hole iliac bone plate in dogs: 95 cases (1996–1999)

Abstract: Results suggest that single-session bilateral triple pelvic osteotomy with 8-hole iliac bone plates is effective for treatment of dogs with bilateral hip dysplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
2
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 12 publications
4
36
2
3
Order By: Relevance
“…Contrary to some investigators who reported that DJD change continues to progress following TPO 11,23 , others indicate that such changes stop after the operation 12,28 . No degenerative changes were observed in any of the animals in our study either before the operation, or at the early or late postoperative follow-up.…”
Section: Discussioncontrasting
confidence: 40%
See 2 more Smart Citations
“…Contrary to some investigators who reported that DJD change continues to progress following TPO 11,23 , others indicate that such changes stop after the operation 12,28 . No degenerative changes were observed in any of the animals in our study either before the operation, or at the early or late postoperative follow-up.…”
Section: Discussioncontrasting
confidence: 40%
“…Borostyankoi et al 23 report that the majority of their 95 dogs could stand 24 h after undergoing a bilateral TPO; the average length of hospitalization was 7.5 days. In this study, we observed that, owing to the unilateral nature of the interventions, all cases could stand without help 24 hours after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Com base em experimentos anteriores (Borostyankoi et al 2003) é possível que se realizando apenas ostectomias bilaterais do púbis, poder-se-iam liberar os segmentos acetabulares. Esses autores realizaram OPT bilateralmente utilizando apenas três osteotomias (duas nos corpos ilíacos e outra na sínfise pélvica); a osteotomia do púbis foi realizada retirando-se uma cunha, com limites de 5mm de cada lado da sínfise púbica na porção cranial do púbis, que se estendeu até a 5mm cranialmente à borda cranial do forâmen obturador.…”
Section: Resultsunclassified
“…El tiempo de formación de callo óseo fue menor a las ocho semanas reportado por Borostyankoi et al (2003) en 95 canes de 10.8 meses de edad y del tiempo de 3-4 meses reportado por Altunatmaz et al (2003) en 31 canes de 6 a 16 meses, para la curación de la osteotomía iliaca en la técnica de triple osteotomía pélvica donde usaron placas de Slocum como medio de estabilización. Asimismo, el apoyo del miembro con capacidad de soporte de peso en el día 13 postquirúrgico en todos los canes fue menor a los 20-25 días reportado por Altunatmaz et al (2003).…”
Section: Discussionunclassified